8 - Quality Assurance Self-assessment: A Catalyst at Aga Khan University - Dhamani, Khairunnisa; Khamis, Tashmin (Journal of Higher Education in Africa, 2022)
This article describes the establishment of the Aga Khan University’s Network of Quality Assurance and Improvement in promoting the principles of quality in its programmes. As an international university, the experiences and lessons learned have the potential to inform quality assurance and improvement in similar contexts. The authors reflect on past attempts to improve the quality of educational offerings, which were primarily traditional quality assurance audits. With the advent of the Inter-University Council for East Africa self-assessment process, the next generation of quality assurance and improvement was launched for the Aga Khan University programmes. They found the self-assessment process effective in changing attitudes towards quality enhancement and implementation of improvement plans, because it created ownership in the process. Practically, self-assessment is an important tool for academic quality assurance providing critical feedback, and catalysing action. The article will be useful for those establishing quality teaching and learning units across multi-site, multi-campus universities, especially in resource challenged environments.